Ответы и объяснения

Лучший Ответ!
2013-04-27T15:47:23+00:00

√3 sin2x + 3cos2x = 0

sin2x = √ (1-cos^2(2x)) 

√ 3√(1-cos^2(2x)) + 3cos2x = 0  замена переменной  t=cos2x

√ (3(1-t^2)) + 3t = 0

√ (3(1-t^2)) = 3t  обе части в квадрат

3(1-t^2) = 9t^2

1-t^2 = 3t^2

1 = 4t^2

t^2= 1/4

t1 =-1/2

t2=1/2

проверим корни подстановкой в исходное выражение

t2=1/2   - не подходит

t1 =-1/2-     подходит

cos2x = t1 =-1/2 

x =pi*n -pi/3 , n E Z

x =pi*n +pi/3 , n E Z

ОТВЕТ

x =pi*n -pi/3 , n E Z

x =pi*n +pi/3 , n E Z